Analysis and control of slope stability of end wall coal mining in Anjialing Open-pit Mine - HOU Chengheng (Meikuang Anquan, 2022)
In order to solve the coal pressing problem of the end-to-boundary slope of Anjialing Open-pit Mine, combined with the actual situation of the north slope to the boundary of Anjialing Open-pit Mine, the sensitivity between the mining height, the overall slope angle and the slope stability is analyzed by using the limit equilibrium method, and the relationship between the horizontal mining internal discharge tracking distance, the internal discharge presser foot height and the slope stability is studied by using the three-dimensional numerical simulation method. The results show that, the mining height is reduced from 1 276 to 1 264, the overall slope angle is increased from 34° to 35°, and the slope stability coefficient is the most sensitive. Through comprehensive analysis, it is determined that the stoping height is 1 264 m level and the overall slope angle is 35° for the stoping scheme of end-side pressing coal; the tracking distance of inner drainage in horizontal mining is 30 m, the height of inner drainage presser foot in horizontal mining is 24 m, which can realize the safe and efficient recovery of coal resources, and it has higher social benefits.